A Randomized Double-Blind Placebo-Controlled Trial Evaluating the Efficacy of Oral Cholecalciferol in Improving Renal and Vascular Functions in Vitamin D-Deficient Patients With Type 2 Diabetes Mellitus. (2nd January 2023) - Das, Saibal; Selvarajan, Sandhiya; Kamalanathan, Sadishkumar; Parameswaran, Sreejith; Zachariah, Bobby
Abstract: This study was performed to evaluate the efficacy of cholecalciferol in improving renal and vascular functions in vitamin D-deficient patients with type 2 diabetes mellitus (T2DM) along with chronic kidney disease (CKD). One hundred patients (18 − 65 years), having T2DM along with CKD (stage IIIA and IIIB) and hypovitaminosis D were randomized (1:1) to receive either oral cholecalciferol 60, 000 IU (Group A) or placebo (Group B) weekly for 8 weeks along with standard background treatment. They were followed up for another 24 weeks. Various parameters of renal and vascular functions were compared. Except for serum calcium and phosphate levels which were significantly higher in Group A ( p < 0.001), there was no significant difference in any of the biochemical or vascular parameters between the two groups at 8 weeks. There were comparable changes in urinary albumin–creatinine ratio and carotid-femoral pulse wave velocity in the two groups at 8 and 24 weeks. There was no improvement in any of the vascular parameters from the corresponding baseline values in the two groups at 8 and 32 weeks. No improvement in renal and vascular functions was observed following treatment with oral cholecalciferol in patients with T2DM and CKD.